Perioperative HDR Brachytherapy for Reirradiation in Head and Neck Recurrences: Single-institution Experience and Systematic Review. Issue 6 (November 2017) - Tagliaferri, Luca; Bussu, Francesco; Fionda, Bruno; Catucci, Francesco; Rigante, Mario; Gambacorta, Maria Antonietta; Autorino, Rosa; Mattiucci, Gian Carlo; Miccichè, Francesco; Placidi, Elisa; Balducci, Mario; Galli, Jacopo; et al.
Aim: The aim of our study was to evaluate the outcomes of patients reirradiated with high-dose-rate (HDR) intensity-modulated brachytherapy (IMBT) for recurrent head and neck cancer and to perform a systematic review of the literature. Materials and Methods: Patients treated with prior radiation doses >65 Gy were considered. After resection of macroscopic disease, catheters were fixed to the tumor bed. The total dose was 30 Gy in 12 fractions of 2.5 Gy twice daily for 5 days a week. A systematic literature search was conducted through several electronic databases including Medline/PubMed, Scopus, Embase and the Cochrane library. Results: Seventeen patients were included; median overall survival was 19 months with a median local control interval of 15 months. Median follow-up was 36 months. Seven papers were considered for the review. Conclusions: IMBT could play an important role in the retreatment of recurrent head and neck cancer.